2016
DOI: 10.1111/1750-3841.13314
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet‐C Light Sanitization of English Cucumber (Cucumis sativus) Packaged in Polyethylene Film

Abstract: Food safety is becoming an increasing concern in the United States. This study investigated the effects of ultraviolet-C (UV-C) light as a postpackaging bactericidal treatment on the quality of English cucumber packaged in polyethylene (PE) film. Escherichia coli k-12 was used as a surrogate microbe. The microbial growth and physical properties of packaged cucumbers were analyzed during a 28-d storage period at 5 °C. Inoculating packaged cucumbers treated at 23 °C for 6 min with UV-C (560 mJ/cm(2) ) resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Also, the penetration depth of the UV-C light on the solid food products could be less deep compared to clear the liquid food products, which affected the destruction of microorganisms below the surface of the paneer. The authors reported that the application of UV-C light irradiation could be used for the surface decontamination of fresh food products and factors such as food product surface characteristics, and location of organisms were found to play significant role [33]. The inactivation of inoculated Penicillium roqueforti and Listeria monocytogenes was studied in the packed and unpacked cheeses by UV-C light application and reported reductions of 1.32 log and 1.24 log in packed and unpacked cheeses [34].…”
Section: Effect Of Uv-c Light On Microbiological Qualities Of Paneermentioning
confidence: 99%
“…Also, the penetration depth of the UV-C light on the solid food products could be less deep compared to clear the liquid food products, which affected the destruction of microorganisms below the surface of the paneer. The authors reported that the application of UV-C light irradiation could be used for the surface decontamination of fresh food products and factors such as food product surface characteristics, and location of organisms were found to play significant role [33]. The inactivation of inoculated Penicillium roqueforti and Listeria monocytogenes was studied in the packed and unpacked cheeses by UV-C light application and reported reductions of 1.32 log and 1.24 log in packed and unpacked cheeses [34].…”
Section: Effect Of Uv-c Light On Microbiological Qualities Of Paneermentioning
confidence: 99%
“…Technological advancements have resulted in the development of UV-C irradiation devices that create a turbulent flow which allows for effective irradiation of opaque fluids of high viscosity. These UV devices have been widely used in the food industry for the treatment of complex opaque liquids or other substances including juices [49][50][51][52][53], tea [54], milk [55][56][57], cheese [58], wine [51], egg [59], dried seafood [60] and sliced fruits and vegetables [61][62][63][64]. UV-C irradiation technology has also been used for the inactivation of several viruses in human plasma products [65][66][67][68][69][70][71].…”
Section: Ultraviolet Light Irradiationmentioning
confidence: 99%
“…The efficacy of UV-C based sterilization is affected by surface properties namely surface roughness. This method is more efficient on the smooth surfaces of kits, fruits and vegetables [22] . On the other hand, heating can kill or inactivate the pathogens even in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%